2014
DOI: 10.1590/s1984-29612014080
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of antibodies against Sarcocystis neurona and Neospora caninum in domestic cats in the state of Bahia, Brazil

Abstract: Sarcocystis neurona is the major agent of equine protozoal myeloencephalitis. It infects several mammalian species in the Americas, where the definitive hosts, marsupials of the genus Didelphis (D. virginiana and D. albiventris) are found. Domestic cats are one of the confirmed intermediate hosts of the parasite; however, antibodies against S. neurona had never before been demonstrated in Brazilian cats. The aim of this study was to determine whether cats in Bahia, Brazil, are exposed to the parasite. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…However, the frequency of antibodies against Neospora spp. was similar to that reported by Sousa et al (2014) in Mato Grosso do Sul (6.6%; 10/151), by Lima et al (2018) on the Island of Fernando de Noronha (3.11%; 8/257), and by Meneses et al (2014) in Bahia (2.9%; 8/272). Therefore, the percentage of frequency of Neospora spp.…”
Section: Regardingsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the frequency of antibodies against Neospora spp. was similar to that reported by Sousa et al (2014) in Mato Grosso do Sul (6.6%; 10/151), by Lima et al (2018) on the Island of Fernando de Noronha (3.11%; 8/257), and by Meneses et al (2014) in Bahia (2.9%; 8/272). Therefore, the percentage of frequency of Neospora spp.…”
Section: Regardingsupporting
confidence: 90%
“…Only two animals had titers above the 1:25 cutoff, demonstrating, in addition to the small number of infected animals, a low rate of seroconversion, corroborating the results of another study (Sedlák, Bartova, & Machacova, 2014). According to Meneses et al (2014) and Feitosa et al (2014), natural infections in cats by Neospora spp. have never been reported, which could suggest low seroconversion or resistance to the pathogen, despite reports of experimental infection in immunosuppressed animals.…”
Section: Regardingsupporting
confidence: 81%
“…shed by opossums were seropositive. Although seropositivity was similar in these two studies, Koch et al (2019) obtained a maximum titer of 100, while Meneses et al (2014) observed 800 as the maximum titer (Table 3). As in dogs, no association with neurological signs was reported for the seropositive cats.…”
Section: /22mentioning
confidence: 57%
“…It is worth mentioning that all the cats tested were from urban areas and they probably had lower exposure to S. neurona sporocysts than cats from rural areas. Subsequently, two studies using IFAT found that 4% (Meneses et al, 2014) and 7% (Koch et al, 2019) of the cats References: SAT: Sarcocystis agglutination test; IFAT: Indirect Fluorescent Antibody Test.…”
Section: Sarcocystis Neurona Infection or Exposure In Domestic Carnivores And In Wildlifementioning
confidence: 99%
“…Several reports on S. neurona infections or exposure in Brazilian animals have been conducted using North American strains of the parasite (39)(40)(41)(42)(43). It is worth to note that S. neurona antigen derived from Brazilian isolates of the parasite is not available for serological tests.…”
Section: Discussionmentioning
confidence: 99%